2009
DOI: 10.1002/jhm.427
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of 30‐day postdischarge hospital readmission or emergency department (ED) visit rates in high‐risk elderly medical patients through delivery of a targeted care bundle

Abstract: Care coordination has shown inconsistent results as a mechanism to reduce hospital readmission and postdischarge emergency department (ED) visit rates. OBJECTIVE:To assess the impact of a supplemental care bundle targeting high-risk elderly inpatients implemented by hospital-based staff compared to usual care on a composite outcome of hospital readmission and/or ED visitation at 30 and 60 days following discharge. PATIENTS/METHODS:Randomized controlled pilot study in 41 medical inpatients predisposed to unplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
298
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(311 citation statements)
references
References 44 publications
3
298
1
3
Order By: Relevance
“…Research has connected some readmissions with potentially modifiable factors, 4,6,20 -such as lack of patient education on discharge, unmet functional needs, and poor access to care-to which physicians treating readmitted patients should devote particular attention. Several multidisciplinary discharge interventions to prevent hospital readmissions have been developed, [21][22][23] and our data support additional efforts oriented specifically toward the communitydwelling geriatric population. Looking beyond the scope of this study, future research should investigate potential causes of recurrent hospitalization, such as worsening medical Our study has some notable limitations.…”
Section: Discussionsupporting
confidence: 65%
“…Research has connected some readmissions with potentially modifiable factors, 4,6,20 -such as lack of patient education on discharge, unmet functional needs, and poor access to care-to which physicians treating readmitted patients should devote particular attention. Several multidisciplinary discharge interventions to prevent hospital readmissions have been developed, [21][22][23] and our data support additional efforts oriented specifically toward the communitydwelling geriatric population. Looking beyond the scope of this study, future research should investigate potential causes of recurrent hospitalization, such as worsening medical Our study has some notable limitations.…”
Section: Discussionsupporting
confidence: 65%
“…61 In a recent metareview, Mistiaen and colleagues 24 retrieved systematic reviews published between 1994 and 2004 that assessed effectiveness of peridischarge interventions aimed at reducing postdischarge problems in adults discharged home from acute general hospital care. Of 15 reviews selected, only three showed reductions in readmissions and all three 22,54,62 were characterised by the combination of patient education and preand postdischarge support.…”
Section: Studies Of Integrated Pre-and Postdischarge Multicomponent Imentioning
confidence: 99%
“…2 They are more likely to be non-English speakers, 3 have lower health literacy, which can impair selfmanagement; [4][5][6] higher rates of mental health and substance abuse disorders; 7 greater exposure to social stressors; 6 and are more likely to experience hospital readmission. [8][9][10] Several care transitions programs [11][12][13][14][15][16] have demonstrated success in decreasing hospital readmissions. These programs have primarily targeted elderly Medicare populations or patients with high risk diagnoses, such as heart failure.…”
Section: Introductionmentioning
confidence: 99%